Evaluation of the strain gradient effect on compressive failure of CRFP composites - Tobias Bianchi; Jawad Naciri; Joël Serra; Christophe Bouvet; Léon Ratsifandriahana (Composites Part C: Open Access)
A pin-ended buckling test inspired by Wisnom [1] was developed to evaluate the effect of strain gradient on the compressive failure strain of composite laminates. Tests were conducted on unidirectional (UD) carbon/epoxy AS4/8552, and strain measurements were obtained using digital image correlation. Various cross-ply stacking sequences, [(0/90)₂]S, [(0/90)₄]S, [(0/90)₈]S, were studied and most specimens failed on the tension side due to the high compressive strength facilitated by the strain gradient, while the tensile failure strain remained unaffected by the strain gradient. To induce failure on the compression side, a novel method was developed by manufacturing bi-material specimens with an aluminum 2024 ply added to the tension side. This modification led to all bi-material specimens failing on the compression side. The results showed a Nnar increase in compressive failure strain as a function of the strain gradient. Furthermore, values reaching up to -33,000 microstrains were obtained for the thinner specimens, which is >2.5 times the compressive failure strain of -12,500 microstrains announced by the manufacturer. This behavior is new compared to other published results obtained on similarly tested materials that demonstrated a linear trend.